The Reaction of Investors and Stock Prices to Insider Trading - CORNELL, BRADFORD; SIRRI, ERIK R. (Journal of Finance, 1992)
ABSTRACT Trading by corporate insiders and their tippees is analyzed in Anheuser‐Busch's 1982 tender offer for Campbell Taggart. Court records that identify insider transactions are used to disentangle the individual insider trades from liquidity trades. Consistent with previous studies, insider trading was found to have had a significant impact on the price' of Campbell Taggart. However, the impact of informed trading on the market is complicated. Trading volume net of insider purchases rose. Contrary to the broad implications of adverse selection models, Campbell Taggart's liquidity improved when the insiders were active in the market, and the insiders received superior execution for their orders.